PARADOKS PENGUNGSI: ANTARA PERLINDUNGAN HAM DAN KEDAULATAN NASIONAL DALAM KRISIS KEMANUSIAAN - Dani Achnisundani; Burhan Fajri Arfian, Tarsisius Susilo, Zulkifli, Wahyu Tunggul Wiratama (JOURNAL OF LAW AND NATION, 2025)
The global refugee crisis presents a paradox for states: they are bound to uphold the human rights of refugees, yet they seek to safeguard national sovereignty and security. This article examines the delicate balance between international refugee protection principles—particularly the non-refoulement obligation—and the sovereign right of states to control their territory. Through normative analysis and case studies in Indonesia and the ASEAN region (including responses to Rohingya refugees, Afghan refugees in Indonesia, and the East Timor and West Papua crises), we explore the dilemma between global humanitarian obligations and national interests. The discussion covers international humanitarian law and human rights principles on refugees, state sovereignty in regulating asylum, regional practices in Indonesia/ASEAN, and the role and challenges of international organizations (UNHCR, IOM, ASEAN). The findings indicate that the non-refoulement principle, as a jus cogens norm, places an absolute limit on sovereignty: states must not return refugees to face persecution or danger. However, national security concerns often drive states to adopt restrictive measures, such as detention or push-backs. Indonesia and other ASEAN states typically employ ad-hoc approaches—offering temporary humanitarian protection while avoiding permanent commitments perceived to affect national interests. The article concludes that a strategic framework is needed to uphold human rights values (including non- refoulement) in harmony with the maintenance of national sovereignty, through stronger regional cooperation, targeted security management (focusing only on high-risk individuals), and enhanced national institutional capacity to manage refugees humanely.